Testing Messages on Facebook to Promote Use of an HPV Educational Web-Intervention - Reno, Jenna E.; Dempsey, Amanda F. (Frontiers in Digital Health, 2021)
In the US, the human papillomavirus (HPV) vaccine remains underutilized leading to disparities in HPV-related diseases. Latinx have some of the highest rates of cancer caused by HPV. In a previous study, we developed a tailored-messaging based online educational intervention (CHICOS) that was found to increase HPV vaccination intention among Latinx participants. The current research uses Facebook Advertising to test the comparative effectiveness of messages designed using the Extended Parallel Processing Model (EPPM) to promote the use of CHICOS among Latinx young adults and parents of adolescents. We also looked at differences in the effectiveness of messages that highlighted HPV-related cancers, genital warts, or a control condition as well as differences in Spanish vs. English messages. Results found Latinx young adults and parents, were more likely to click on Facebook Advertisements containing messages in Spanish and those that mention cancer risks pertinent to this population compared to those in English or messages that discuss genital warts. Thus, findings suggest that Facebook Advertising has the potential to be a useful tool for motivating information seeking online about HPV vaccination.